Colonial Frames: the construction of racist imagery surrounding black motherhood between the past and the present (Cadernos de Sociomuseologia, 2025)
This article proposes an analysis of the visual representations of motherhood attributed to Black women in the context of the colonial past, which contributed to the construction of a collective imagination with a racist bias—whose effects still resonate today. As a starting point, two wool dolls—one Black and one white—were selected from the temporary exhibition Pluralidade (Plurality), held at the Museum of Sacred Art in the Municipality of Covilhã, Portugal. Using a discourse analysis approach, the study aims to understand how the narrative of these two pieces is constructed within an exhibition that claims to address diversity. The analysis seeks to uncover the meanings produced around these works, critically relating them to other representations of the Black mother figure in various narrative spaces—especially those structured by prejudiced logics, such as the traditional-normative European museum. The term “colonial frame” is used as a guide to interpret the meanings attributed to Black women's motherhood, both in the past and in ongoing everyday practices. Thus, the article discusses how racial issues are often reinforced in museum spaces, even when there is an intention to promote narratives of diversity—particularly when such narratives are developed without the inclusion of Black voices in representing their own bodies. In this way, it is argued that the pursuit of plurality, when mediated exclusively through white lenses, ends up reproducing the very prejudices that the exhibition claims to challenge.Keywords: Motherhood; Black Women; Museums; Racism.